Capital Structure and Financial Performance of Listed Manufacturing Goods Firms in Nigeria - WORLU, CHRISTIAN NWENEDA (Ph.D); ZORKPA, CHARLES BARINEM (Ph.D) (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
This study investigated capital structure and financial performance of listed industrial goods firms in Nigeria. The dwindling rate of business operations which has affected the revenue base of the listed industrial goods firms in the Country necessitated this study. The sample size for the study consisted of thirteen (13) listed industrial goods firms in Nigeria. The study made use secondary data. The secondary data was obtained from the listed industrial goods firm’s annual reports and accounts. Data was analyzed using descriptive and Pearson correlation coefficient statistical tools with the aid of statistical package for social sciences. The findings reveal that equity capital has a positive strong relationship with return on asset in the listed industrial goods firms in Nigeria and also debt capital was found to have very strong relationship with return on asset. Based on the findings, it was concluded that capital structure significantly affects financial performance. Therefore, the study recommends that listed industrial goods firms in Nigeria should employ more equity finance in establishing optimal capital structure. Finally, when capital is raised through debt instrument, more attention should be channeled towards other areas for performance enhancement instead of relying on returns from equity capital alone.